DESCRIPTION OF PROSOCIAL BEHAVIOR IN YOUNG CHILDREN WITH INTELLECTUAL DISABILITY IN EAST NUSA TENGGARA - Kiling-Bunga, Beatriks Novianti; Ngawas, Kresensia Wea Aga; Kiling, Indra Yohanes (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2016)
Abstract — World Health Organization and United Nations Children’s Fund have stated in year 2012 that one of their global agenda is to fulfill the needs of inclusive Early Childhood Care and Development (ECCD) to increase the participation and development of young children with disabilities. One of important things for the agenda are understanding various special needs of young children with various kind of mental disability, such as mental retardation or nowadays known as intellectual disability. This research aims to narratively describe the prosocial behaviors of a young child with intellectual disability in special school of Pembina Kupang, East Nusa Tenggara. This research used qualitative approach with child observation and interview to the parents as the main technique to gather data. This research shows that prosocial behaviors in young children with intellectual disability are divided into four aspects, those are: a) the ability to join groups, b) supportive acts, c) empathy and caring, and d) self-adjustment. These behaviors were shown in the child’s daily activities, her habits, affected by the culture and daily activities of her parents and siblings, and also by the interaction with her friends and family. This research could give important information about the importance of managing the social interaction in inclusive ECCD by putting emphasis in four aspects described above, and also the role of parents and ECCD tutors in facilitating activities that could help stimulate specific needs of social skills in young children with intellectual disability. Abstrak — World Health Organization dan United Nations Children’s Fund telah menyatakan pada tahun 2012 bahwa agenda global mereka adalah untuk memenuhi kebutuhan Pendidikan Anak Usia Dini (PAUD) inklusif, salah satunya untuk meningkatkan partisipasi dan perkembangan anak-anak dengan disabilitas. Salah satu hal penting untuk agenda ini adalah pemahaman terhadap berbagai kebutuhan khusus anak-anak dengan berbagai jenis disabilitas mental, seperti retardasi mental atau saat ini dikenal sebagai disabilitas intelektual. Penelitian ini bertujuan untuk menggambarkan secara naratif mengenai perilaku prososial anak muda dengan disabilitas intelektual di sekolah khusus Pembina Kupang, Nusa Tenggara Timur. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan observasi pada anak dan wawancara dengan orangtua, sebagai teknik utama untuk mengumpulkan data. Penelitian ini mendapatkan bahwa perilaku prososial pada anak-anak dengan disabilitas intelektual dibagi menjadi empat aspek, yaitu: a) kemampuan untuk bergabung dengan grup, b) tindakan yang mendukung perilaku prososial, c) empati dan peduli, serta d) penyesuaian diri. Perilaku ini ditunjukkan dalam kegiatan sehari-hari anak, kebiasaannya, dipengaruhi oleh budaya dan kegiatan sehari-hari dari orangtua dan saudaranya, juga oleh interaksi dengan teman-teman dan keluarganya. Penelitian ini dapat memberikan informasi penting tentang pengelolaan interaksi sosial dalam PAUD inklusif dengan menempatkan penekanan dalam empat aspek yang dijelaskan di atas, dan juga peran orangtua dan pengajar PAUD dalam kegiatan yang bisa membantu merangsang kebutuhan spesifik dari keterampilan sosial pada anak-anak dengan disabilitas intelektual.